2018
DOI: 10.4236/health.2018.109088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 528 Hz Music on the Endocrine System and Autonomic Nervous System

Abstract: This study examined the stress-reducing effect on the endocrine system and the autonomic nervous system of music with a frequency of 528 Hz, which has recently attracted attention as a "healing" type of music. Nine healthy participants (one man and eight women, aged 26 -37 years) listened to 528 Hz and standard 440 Hz music on separate days. We measured salivary biomarkers of stress (cortisol, chromogranin A, and oxytocin) before and after exposure to music, and continuously recorded the activity of the autono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…Listening to music has been shown to reduce social stress and temper aggression in others [7]. The use of music that consisted of frequencies identified as Solfeggio sounds may have been stress reducing [8]. There was no instrument used to measure the physiological changes in mood associated with stress reduction amongst the Zoom classroom participants.…”
Section: Health and Wellnessmentioning
confidence: 99%
“…Listening to music has been shown to reduce social stress and temper aggression in others [7]. The use of music that consisted of frequencies identified as Solfeggio sounds may have been stress reducing [8]. There was no instrument used to measure the physiological changes in mood associated with stress reduction amongst the Zoom classroom participants.…”
Section: Health and Wellnessmentioning
confidence: 99%
“…There is a need to understand how much stress impacts an individual's person and how they think which could aid the designers to come up with a proper guideline to build an application. At the same time, there is no one specific music that could satisfy and help all users to reduce stress, which is why there will be a few suggestions available in the application, which are Solfeggio frequencies [4,5] and binaural beats [6]. Detecting stress using methods like Stress Test is also time consuming and requires individual's stress level.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the relative lack of conclusive findings in the field of pain management, musical characteristics such as sound intensity, tempo, timbre, and arousal level have been shown to affect ANS activity in a plethora of studies ( 62 68 ). However, only recently, audio frequencies, which constitute another inherent feature of music, have been brought into focus of scientific investigations ( 69 72 ). From a technical perspective, the term frequency describes the number of oscillations per time unit, i.e., for audio frequency, it is the number of vibrations per second that determines the pitch of a sound and is measured in Hertz (Hz).…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that particularly the modulation of high-frequency components was more effective in supporting autonomic recovery compared to the other conditions. In another study, Akimoto et al ( 69 ) tested so-called “solfeggio frequency music.” In their study, nine participants listened to 5 min of “regular” relaxing piano music, i.e., tuned to the international standard reference tone of 440 Hz, on 1 day, and to the same piece tuned to a reference tone of 444 Hz (which results in the inclusion of 528 Hz), on a different day. Biomarkers of the ANS were assessed during and after exposure to music.…”
Section: Introductionmentioning
confidence: 99%